St. Anthony’s Church grounds in Versova village - Mumbai Archive Project Team (Jio Institute, 2024)
The festival is held at St. Anthony’s Church grounds in Versova village. It comes to life at night when the crowd swells and business peaks. In addition to food stalls, crowds enjoy live music, cultural performances, and other entertainment activities and programmes that last until midnight.